THE NEW SOCIAL REALITY AND SOCIO-PSYCHOLOGICAL TRANSFORMATIONS OF VALUES - Alaverdyan, N. A. (Modern Psychology, 2022)
At present, when the world is in transformation, a fresh interpretation of social-cultural function of values in construction and regulation of social life, social-cultural principles of coexistence, transferring of life-experience and formation of national identity have acquired a new theoretical and prac- tical significance. Social life on the one hand is characterized by stable sys- tems of values, norms, traditions and ideas that regulate relations, which enable the society to maintain its qualitative specificities, and on the other hand, it is characterized by continuous change and renewal. Social systems exist thanks to new sociocultural values, which provide the existence of the society and its development. The difficult process of combining old and new realities creates a precondition for the formation of a dichotomous worldview and dual social positions. During various historical periods, social systems survive because thanks to certain mechanisms they are supplemented with new sociocultural values. Modern society becomes more and more pluralistic and alternative and creates such moral-psychological atmosphere, when a person does not only feel cultural inferiority, but also becomes more adaptable to new attitudes and lifestyles. Old, tested values and norms regulating peoples thoughts and behavior clash with new, unfamiliar values. In this process on the one hand the conservativeness ensures stability within the society, and on the other, modernity adopts new values and aims at mobility and innovation. Under such conditions of radical transformations values fulfill the important function of overcoming social- cultural crises, adaptation to new conditions, reduction of struggle between the old and the new. From this point of view, values is not only stable and reliable basis for society, but also for its renewal and modernization.
Keywords: sociocultural values,; unpredictability; uncertainty; modernization,; consumer values; dichotomous worldview; transformation.